Internet Gaming Disorder Increases Mind-Wandering in Young Adults - Zhang, Jiawen; Zhou, Hui; Geng, Fengji; Song, Xiaolan; Hu, Yuzheng (Frontiers in Psychology, 2021)
As a primary symptom defining Internet gaming disorder (IGD), preoccupation indicates a mind-state in which gamers think about gaming activity so much that other things appear less important and/or interesting to them. Previous studies have examined the negative impacts of IGD on both cognitive and affective functions, yet no study has investigated the influence of IGD on daily mind-state changes that interfere with ongoing tasks. The current study hypothesized that more IGD symptoms leads to higher frequency of mind-state shift in terms of mind-wandering. As social anxiety is related both IGD and mind-wandering, we further hypothesized that social anxiety would partially contribute to the relationship. Survey data were collected from 632 young adults who were divided into two groups based on whether they reported playing games or not. In the player group, the number of IGD symptoms present was positively related to mind-wandering (r = .269, p < .001) and social anxiety (r = .235, p < .001), with the latter two showing positive correlation in both players (r = .37, p < .001) and non-players (r = .57, p < .001). A mediation analysis for the players showed a partial mediation effect of social anxiety on the relationship between IGD and mind-wandering (mediation effect: PM = .292, p < .001), and the model was replicated in an independent sample. This study suggests that excessive gaming behavior may increase mind-wandering and a shift towards such a non-productive mind-state could exert long-term detrimental effects in adolescents and young adults.